Kinetic modeling of the inverse suspension production of acrylic gels using in line FTIR-ATR monitoring and off-line SEC/RI/MALLS product characterization - Gonçalves, Miguel A.D. (2010)
This work describes the production of acrylic gels in a batch stirred reactor at 1.5 dm3 scale. Inverse suspension technique is used within this purpose. Paraffin (P) was used in the continuous phase and polymer networks were synthesized in the dispersed phase containing water (W) dissolved acrylic acid (AA), trimethylolpropane triacrylate (TMPTA), used as crosslinker, and 2,2’-azobis(2-methylpropionamidine) dihydrochloride (V50) as a free radical initiator.